1989
DOI: 10.1007/bf00736065
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-selective up-regulation of human saphenous vein \2-adrenoceptors by chronic \-adrenoceptor antagonist treatment

Abstract: To study beta-adrenoceptor antagonist-induced changes in human vascular beta-adrenoceptors, we determined the effects of chronic treatment with different beta-adrenoceptor antagonists without intrinsic sympathomimetic activity (ISA) on beta 2-adrenoceptor density (assessed by (-)-[125I]-iodopindolol binding) in human saphenous vein membranes obtained from patients undergoing coronary artery bypass grafting. In patients chronically treated with the non-selective beta-adrenoceptor antagonists propranolol or sota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…NS β-Blocker patients treated with nonselective β-AR blocker propranolol and sotalol; β 1 -Blocker patients treated with the β 1 -AR selective blocker metoprolol, atenolol and bisoprolol. Modified from Michel et al (1988) and Brodde et al (1989) 1998). CHF patients show marked reduction in the positive force-frequency relationship (for references, see Just 1996) and no augmentation by β-AR stimulation (Bhargava et al 1998).…”
Section: Effects On Force-frequency Relationshipmentioning
confidence: 99%
“…NS β-Blocker patients treated with nonselective β-AR blocker propranolol and sotalol; β 1 -Blocker patients treated with the β 1 -AR selective blocker metoprolol, atenolol and bisoprolol. Modified from Michel et al (1988) and Brodde et al (1989) 1998). CHF patients show marked reduction in the positive force-frequency relationship (for references, see Just 1996) and no augmentation by β-AR stimulation (Bhargava et al 1998).…”
Section: Effects On Force-frequency Relationshipmentioning
confidence: 99%
“…The human dorsal hand vein contains both band aadrenoceptors [1][2][3] and there is evidence that both a 1 -and a 2 -adrenoceptors mediate constrictor responses [3,4] and b 2 -adrenoceptors mediate dilator responses [3,5]. It is and nonselective adrenoceptor agonists.…”
Section: Introductionmentioning
confidence: 99%
“…The human dorsal hand vein contains both β‐ and α‐adrenoceptors [1‐3] and there is evidence that both α 1 ‐ and α 2 ‐adrenoceptors mediate constrictor responses [3, 4] and β 2 ‐adrenoceptors mediate dilator responses [3, 5]. It is more controversial, however, whether there are also venodilator β 1 ‐adrenoceptors in the dorsal hand vein.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, He and colleagues 28 found only moderate arterial relaxation in response to isoproterenol (beta 1 and 2 adrenergic agonist) and concluded that betaadrenoreceptors would contribute little to the reactivity of the human ITA graft to sympathomimetic drugs. Brodde and colleagues 29 demonstrated the subtype-selective upregulation of beta-2 adrenergic receptors in the heart muscle and the SV by chronic beta-adrenoreceptor antagonist treatment. However, Ferro and colleagues 30 did not find a change in beta-1 or beta-2 reactions, or the alpha-1 adrenergic reaction in ITA and SV segments from patients chronically treated with beta-blockers.…”
Section: Discussionmentioning
confidence: 99%